MEMPERBAIKI CITRA NEGATIF BIROKRASI INDONESIA - Rahmawati Rahmawati (Jurnal Administrasi Publik, 2010)
In public service, a very strong orientation of power during the New Order has made the bureaucracy became increasingly distant from its mission to provide public services. Bureaucracy and its officials more authority than the position itself as a public servant. Negative image of public bureaucracy today is inseparable from the history of the formation factor bureaucracy itself. In addition to that, the culture of the people of Indonesia are more patterned paternalistic make public bureaucracy as a "collection of" family who protect each other. Corruption, collusion, and nepotism is firmly attached to the cirri of the bureaucracy. It makes public bureaucracy into an organization that is difficult to be touched by the people, especially who have no kinship. Negative image of bureaucracy can be eliminated if the government is serious to fix the personnel management of public bureaucracy, empowering communities to supervise the administration and enforcement of strict laws. It is expected to be generated employees of public organizations qualified, competent, clean and free from corruption, collusion and nepotism.